Evaluation of Particle Emissions Emitted from a Light-duty Diesel Vehicle Equipped with Retrofit Ceria and Platinum Partial Flow Diesel Particulate Filters - MyatHsu Thin; Plan Teekatasn Cosh; Poonnut Thaeviriyakul; Phobkrit Kanokkhanarat; Mek Srilom; Chinda Charoenphonphanich; Manop Masomtob; Peerawat Saisirirat; Sompong Srimanosaowa; Watcharin Po-ngaen; Hidenori Kosaka; Preechar Karin (Research Square, 2023)
Abstract With increasingly stringent emissions standards, the reduction of harmful exhaust gases and solid particles has become a primary concern for diesel vehicles. This study focuses on a light-duty vehicle equipped with a 2.5L 4-cylinder common rail direct diesel injection engine, evaluated on a chassis dynamometer under four urban driving cycles and one extra-urban cycle of the new European driving cycle (NEDC). The vehicle's emissions were assessed using B10, B20, and B100 fuels in two scenarios: without a retrofit partial filter diesel particulate filter (P-DPF) and with P-DPFs coated with ceria and platinum. Comparing the use of biodiesel, B100 demonstrated a significant reduction of approximately 50% in particulate mass (PM) and particulate number (PN). Furthermore, the results indicated that the utilization of the partial flow DPF led to a PM emissions reduction exceeding 60% and a particle number reduction of up to 45%. Additionally, the installation of a diesel oxidation catalyst (DOC) resulted in reductions of total hydrocarbon (THC) and carbon monoxide (CO) emissions by up to 59% and 81% respectively, compared to the baseline fuel emissions. However, the installation of the retrofit P-DPF and DOC did not have a significant impact on carbon dioxide (CO2) and nitrogen oxides (NOx) emissions. In terms of catalytic coating, the ceria catalyst emerged as a promising and cost-effective alternative to platinum catalysts for reducing pollutant emissions from diesel vehicles. Overall, this study highlights the effectiveness of utilizing B100 biodiesel and the after-treatment system including P-DPFs and DOCs in mitigating particulate matter and certain gaseous emissions, emphasizing the potential of ceria catalysts as a viable option in emission reduction strategies for diesel vehicles.
Keywords: Catalytic Processes in Materials Science; Vehicle emissions and performance; Biodiesel Production and Applications